Industrial Clusters and Nearshoring in Mexico: A Strategic Framework for Economic Repositioning - Hernández, Armando Pacheco; Bonilla-Landaverry, Gesly Anibal (Asian Journal of Science, Technology, Engineering, and Art, 2025)
The objective of this work is to make known the importance of clusters through nearshoring. In Mexico, it is part of several trade agreements, such as the T-MEC (Treaty between Mexico, the United States, and Canada), which facilitates international trade and provides tariff advantages. This may attract companies looking to benefit from these agreements. Mexico has a qualified and competitive workforce in terms of costs. Education and technical training are constantly growing, providing companies with trained human talent. Nearshoring can boost the creation and expansion of industrial clusters in different regions of Mexico. Clusters are geographic concentrations of companies and organizations related to the same sector. These clusters foster innovation and collaboration, increasing synergies and operational efficiency. Mexico has a diversified economy with key sectors such as manufacturing, automotive, technology, and aerospace. Nearshoring can encourage the growth of clusters in these sectors, promoting innovation and technological development. Mexico has shown economic stability and has policies to support industrial and technological development. The government has implemented programs to encourage foreign investment and infrastructure development, which can be attractive to companies seeking to establish themselves in the country. Establishing new businesses and expanding existing ones can create jobs and stimulate local economic growth. Clusters encourage collaboration and the exchange of ideas, which can lead to technological advances and greater competitiveness. Regional Development: The creation of clusters can help develop less urbanized regions, better distributing economic opportunities throughout the country.